2011
DOI: 10.1002/imhj.20312
|View full text |Cite
|
Sign up to set email alerts
|

Interactive coordination of currently depressed inpatient mothers and their infants during the postpartum period

Abstract: In healthy mother-infant dyads, interactions are characterized by a pattern of matching and mismatching interactive states with quick reparation of mismatches into matches. In contrast, dyads in which mothers have postpartum depression show impaired mother-infant interaction patterns over the first few months of the infant's life. The majority of studies that have examined such interaction patterns have drawn on community samples rather than on depressed inpatient samples of mothers who were in a state of curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…This was κ = 0.73 for the infant codes and κ = 0.78 for the maternal codes. Thus, the interrater reliability of our study coders was similar to those reported in previous studies [24,51]. …”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…This was κ = 0.73 for the infant codes and κ = 0.78 for the maternal codes. Thus, the interrater reliability of our study coders was similar to those reported in previous studies [24,51]. …”
Section: Methodssupporting
confidence: 74%
“…They were not aware which videos were used for assessing coding reliability. In accordance with other studies [24,51], we used Cohen's κ [52] to compute interrater reliability. This was κ = 0.73 for the infant codes and κ = 0.78 for the maternal codes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants of this study were recruited in the course of a larger longitudinal investigation of mother-infant dyads at the psychiatric University Hospital Heidelberg from September 2001 till November 2006 [for further details, see [24]. The current study included data from the first set of data collection and comprises a sample of 68 mother-infant dyads.…”
Section: Methodsmentioning
confidence: 99%
“…Withdrawn and intrusive interaction styles often exhibited by depressed mothers were found to be associated with adverse infant outcomes, such as a generalized disengaged and passive affectivity and self-regulatory style as well as insecure attachment styles [19,20,21,22,23]. Mother-infant matching can be hampered by maternal depression [22,23,24]. However, findings are inconsistent.…”
Section: Introductionmentioning
confidence: 99%